Midbrain structures and control of ventilation in amphibians - Gargaglioni, L. H.; Branco, L. G.S. (Springer Nature, 2009)
Despite recent advances, the mechanisms of neurorespiratory control in anuran amphibians are far from understood. Among key brainstem structures believed to play a major role in the ventilatory control of amphibians is the nucleus isthmi (NI) and Locus coeruleus (LC). It has been suggested that the NI acts to inhibit hypoxic and hypercarbic drives to breathing. The putative mediators for these responses are glutamate and nitric oxide. As to the LC, it has now been reported that this nucleus is a CO2-sensitive receptor site in amphibians, which mediates the ventilatory response to hypercapnia. This chapter reviews the available data on the role of the NI and LC in the control of ventilation in amphibians.